Aquatic and benthic bacteria responses to feed and fertiliser application in trials with the freshwater prawn, Macrobrachium rosenbergii (de Man) - MacLean, M.H.; Ang, K.J.; Brown, J.H.; Jauncey, K. (1994)
The effects of formulated feed and organic fertiliser on aquatic and benthic bacterial populations and on production of the freshwater prawn Macrobrachium rosenbergii (de Man) were assessed. Prawns were cultured in pond enclosures to which pelleted feed and/or chicken manure were added. Prawn survival was high but growth poor. Total bacterial abundance, mean cell volume and biomass, determined respectively by epifluorescence microscopy, image analysis and conversion calculation, illustrated the effect of treatment on the water and sediment bacterial populations. Differences in bacterial abundance and mean cell size were evident between treatments. The discussion considers the importance of bacterial productivity and food web dynamics. © 1994.